Spatial nitric oxide imaging using 1,2-diaminoanthraquinone to investigate the involvement of nitric oxide in long-term potentiation in rat brain slices - Bohlen und Halbach, Oliver von; Albrecht, Doris; Heinemann, Uwe; Schuchmann, Sebastian (NeuroImage, 2002)
Long-term potentiation (LTP), a model of activity-dependent synaptic plasticity, involves the persistent enhancement of excitatory neurotransmission. Several recent studies have suggested a critical role for nitric oxide (NO) production in hippocampal LTP. However, increase in NO production in living tissue has not yet been directly demonstrated. We used 1,2-diaminoanthraquinone (DAQ) to demonstrate NO production in rat brain slices in relation to induction of LTP. DAQ was found to be without neurotoxic effects and it neither influenced normal evoked field potential amplitudes nor did it affect induction of LTP in comparison to controls. We found that DAQ-induced fluorescence is elevated within a limited area of about 40,000 microm(2) during LTP induction in the hippocampal area CA1. Furthermore, we could demonstrate that application of the NO-synthetase inhibitor l-NAME inhibits the induction of LTP in area CA1 and causes a strong reduction of DAQ induced fluorescence. Our results are consistent with the hypothesis that NO can serve as a retrograde messenger during induction of LTP in the hippocampus.
Gesehen am 23.10.2017